2020
DOI: 10.1038/s41467-020-15331-8
|View full text |Cite
|
Sign up to set email alerts
|

c-di-GMP modulates type IV MSHA pilus retraction and surface attachment in Vibrio cholerae

Abstract: Biofilm formation by Vibrio cholerae facilitates environmental persistence, and hyperinfectivity within the host. Biofilm formation is regulated by 3',5'-cyclic diguanylate (c-di-GMP) and requires production of the type IV mannose-sensitive hemagglutinin (MSHA) pilus. Here, we show that the MSHA pilus is a dynamic extendable and retractable system, and its activity is directly controlled by c-di-GMP. The interaction between c-di-GMP and the ATPase MshE promotes pilus extension, whereas low levels of c-di-GMP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 76 publications
7
81
0
Order By: Relevance
“…Increased c-di-GMP levels lead to binding of c-di-GMP to FlrA, and inhibition of its activity which in turn diminishes flagellar gene expression (Srivastava et al, 2013). The dynamic extension and retraction of the MSHA pilus (Jones et al, 2015;Wang et al, 2016) is regulated by c-di-GMP via interaction with the ATPase MshE (Floyd et al, 2020). The role of c-di-GMP in the regulation of large adhesins which control reversible cell attachment during biofilm formation also highlights the essentiality of the molecule (Kitts et al, 2019).…”
Section: Regulation Of Biofilm Formation In V Cholerae and Pathogenesismentioning
confidence: 99%
“…Increased c-di-GMP levels lead to binding of c-di-GMP to FlrA, and inhibition of its activity which in turn diminishes flagellar gene expression (Srivastava et al, 2013). The dynamic extension and retraction of the MSHA pilus (Jones et al, 2015;Wang et al, 2016) is regulated by c-di-GMP via interaction with the ATPase MshE (Floyd et al, 2020). The role of c-di-GMP in the regulation of large adhesins which control reversible cell attachment during biofilm formation also highlights the essentiality of the molecule (Kitts et al, 2019).…”
Section: Regulation Of Biofilm Formation In V Cholerae and Pathogenesismentioning
confidence: 99%
“…All serotype O1 strains contained the autotransporter adhesion ( TAA ) gene ( Rock & Nelson, 2006 ) and Mannose-sensitive haemagglutinin biogenesis protein MshQ gene ( Floyd et al, 2020 ); none of these genes were found in the serotype O2 or O3 strains. Also, all O1 strains contained the lipase family protein gene ( Rock & Nelson, 2006 ), the heme receptor huvA gene ( Li & Ma, 2017 ), and the toxA gene ( Reyes-Becerril et al, 2016 ); these genes were found in 8%, 71% and 52% of the O2 and O3 strains, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that for cells demonstrating tethered motion, a progressive twisting of the surface-attached pilus fiber during the circular motion of cells may gradually cause the circular motion to stop by pulling the cell body ever closer to the surface. Although twitching has not be observed in V. cholerae , this is one mechanism by which retraction-like dynamics may be achieved ( Charles et al, 2019 ), possibly in tandem with actual retraction of MSHA pili, which has been shown recently in a different strain of V. cholera ( Floyd et al, 2020 ). Under our conditions, we have not observed MSHA pili retraction events nor have we seen bacterial cells that gradually acquire fluorescence when only maleimide dyes were used.…”
Section: Discussionmentioning
confidence: 97%